Superiority of the Hyperbaric Bupivacaine 0.50% Over 0.75% Hyperbaric Bupivacaine in patients Undergoing Electivecesarean Section: A Uni-Center Double Blind Randomized Control Trial - Farrukh Ayub, Bilqees Akhtar Malik, Shahzad Bashir Momina (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study was to compare 0.75% and 0.50% hyperbaric bupivacaine in terms of hemodynamic stability in elective cesarean section. Study Design: Randomized Controlled Trial. Place and duration: Department of Anesthesiology, Intensive care and pain management, Combined Military Hospital, Mardan from September 2021 to March 2022. Methodology: Total 104 women were randomly divided into Group-A (0.50% drug concentration) and Group-B (0.75% drug concentration) hyperbaric bupivacaine. Base line systolic blood pressure was noted. Lumber puncture was done in L3/L4 or L4/L5 space. Reading were taken at 1-min, 3-min, 5-min and 30-min. Drop in SBP<20% from baseline was taken as hemodynamic stability. Stability in SBP systolic blood pressure among the two groups A and B were compared. Results: The mean systolic blood pressure of group A was 123.77±8.43 mmHg while in group B it was 123.66±9.14 mmHg. In group A more than 20% decrease in SBP were noted in 42.3% while in group B it was observed in 63.5% patients. Hemodynamic stabilitywas noted in 57.7% patients and 36.5% patient respectively in study group A and B and difference was significant (p=0.031). Conclusions: The Hyperbaric Bupivacaine 0.50% is found superior than 0.75% interms of hemodynamic stability in patients undergoing elective Cesarean Section. Keywords: Hyperbaric Bupivacaine, Hemodynamic Stability, Elective Cesarean Section